NAVIGATING FATWA-TO-REGULATION TRANSFORMATION IN ISLAMIC FINANCE: CHALLENGES AND INNOVATIONS POST-OMNIBUS LAW 2023 - Asrori S. Karni; Ro’fah Setyowati; Nabitatus Sa'adah; Maula Azharil Adzkia (Fakultas Hukum, Universitas Diponegoro, 2025)
The transformation of fatwas into regulations in the financial sector has been widely studied, but there is a lack of analysis on the dynamics following the 2023 Omnibus Law, particularly regarding the implementation of DSN-MUI Fatwa No. 153/2022 on Early Settlement of Murabahah Debt. This study addresses this research gap by employing a normative legal approach, supplemented by empirical observations at two Islamic financing institutions. The findings reveal that, although the fatwa has been disseminated through three annual forums and incorporated into OJK (Financial Services Authority) guidelines, it has yet to attain legal finality as a binding regulation. The first institution continues to follow the earlier fatwa, citing insufficient legal certainty in the new regulation, and maintains a non-discounted early repayment model. In contrast, the second institution, which has long provided early settlement discounts, finds the OJK guideline’s calculation formula commercially inequitable. As a result, they developed an alternative simulation model to remain Sharia-compliant while ensuring business competitiveness. The novelty of this research lies in its exploration of on-the-ground regulatory interactions and its proposal for a legal codification framework based on feedback from industry stakeholders. This study recommends a more flexible and adaptive model for the fatwa-to-regulation transformation, attuned to operational realities. A sustained tripartite dialogue between fatwa authorities, regulators, and industry players is crucial to navigating field complexities and ensuring that regulations uphold Sharia principles while fostering sustainable business practices.